(untitled) (American Journal of Medical Science and Innovation, 2025)
Crohn’s disease of both varieties (abdominal and perineal) may lead to many surgical complications treated by different procedures. The role of surgery has a paramount importance in treating Crohn’s disease complications despite medical therapy. The purpose of this study is to investigate the indications, types, and outcomes of surgical therapy for Crohn’s disease at gastroenterology and hepatology hospitals. This is a longitudinal sectional prospective study that was conducted in Gastroenterology and Hepatology Hospital from March 2020- May 2022, involves 35 patients of Crohn’s disease were diagnosed relying on clinical, radiological, and histopathological result based on endoscopic biopsy and/or surgical specimen. Current study demonstrated that the most common indication of surgery in abdominal Crohn’s disease cohort is intestinal obstruction with 23 patients (65.71%) treated by ileocecal resection. Intestinal fistula 7 patients (20%). Failure of medical treatment 3 patients (8.57%). Malignancy 2 patients (5.71%). Psoas abscess drainage 1 patient (2.85%). Most common Indication of surgery in peri-anal Crohn’s disease is intractable perianal fistula to medical treatment 5 patients (14.28%), Perianal abscess patients (8.57%). Although the medical treatment is the corner stone in management of Crohn’s disease but early referral to digestive surgeon is preferable to decrease the suffering of the patients and improve the outcome.